Enhancing Arabic Listening Skills through the Development of Interactive Multimedia for High School Students - Halisah, Atikah Nur; Sujaini, Herry; Salam, Urai; Aunurrahman, Aunurrahman; Yani, Ahmad; Queiroz, Carla (Universitas Islam Negeri Raden Intan Lampung, 2025)
Listening comprehension is one of the most challenging skills for students learning Arabic. This research aimed to develop and evaluate an interactive multimedia learning product based on the Lectora Inspire application to enhance Arabic listening skills among high school students. Employing a research and development (R&D) design, the study followed a modified Borg & Gall model integrated with the ADDIE framework. Data were collected through interviews, observations, questionnaires, and pre- and post-tests, and analyzed using the Rasch model, N-Gain score, and Mann–Whitney U test. Validation results indicated very good feasibility across content, design, and interactivity aspects. In the experimental class (n = 32), the mean N-Gain score was 0.6272 (62.72%), categorized as medium-to-high according to Hake’s criteria, indicating substantial improvement in listening skills. Rasch analysis revealed significant increases in logit ability from pretest to posttest, with stable fit indices. The Mann–Whitney U test confirmed a significant difference between the experimental and control groups (p < 0.05). The findings of this study indicated that interactive multimedia developed with the Lectora Inspire application effectively enhances Arabic listening skills among high school students. The integration of text, audio, video, animation, and interactive quizzes created an engaging and multisensory learning experience that improved comprehension and motivation. These results implied that teachers can utilize Lectora Inspire–based multimedia as an innovative, student-centered tool to strengthen listening instruction, while the validated development model may serve as a reference for future multimedia-based Arabic learning materials.